Chromosomal integration of Tn5253 occurs downstream of a conserved 11-bp sequence of the rbgA gene in Streptococcus pneumoniae and in all the other known hosts of this integrative conjugative element (ICE) - Francesco Santoro (BMC, 2021)
Abstract Background Tn5253, a composite Integrative Conjugative Element (ICE) of Streptococcus pneumoniae carrying tet(M) and cat resistance determinants, was found to (i) integrate at specific 83-bp integration site (attB), (ii) produce circular forms joined by a 84-bp sequence (attTn), and (iii) restore the chromosomal integration site. The purpose of this study is to functionally characterize the attB in S. pneumoniae strains with different genetic backgrounds and in other bacterial species, and to investigate the presence of Tn5253 attB site into bacterial genomes. Results Analysis of representative Tn5253-carryng transconjugants obtained in S. pneumoniae strains with different genetic backgrounds and in other bacterial species, namely Streptococcus agalactiae, Streptococcus gordonii, Streptococcus pyogenes, and Enterococcus faecalis showed that: (i) Tn5253 integrates in rbgA of S. pneumoniae and in orthologous rbgA genes of other bacterial species, (ii) integration occurs always downstream of a 11-bp sequence conserved among streptococcal and enterococcal hosts, (iii) length of the attB site corresponds to length of the duplication after Tn5253 integration, (iv) attB duplication restores rbgA CDS, (v) Tn5253 produced circular forms containing the attTn site at a concentration ranging between 2.0 × 10−5 to 1.2 × 10−2 copies per chromosome depending on bacterial species and strain, (vi) reconstitution of attB sites occurred at 3.7 × 10−5 to 1.7 × 10−2 copies per chromosome. A database search of complete microbial genomes using Tn5253 attB as a probe showed that (i) thirteen attB variants were present in the 85 complete pneumococcal genomes, (ii) in 75 pneumococcal genomes (88.3 %), the attB site was 83 or 84 nucleotides in length, while in 10 (11.7 %) it was 41 nucleotides, (iii) in other 19 bacterial species attB was located in orthologous rbgA genes and its size ranged between 17 and 84 nucleotides, (iv) the 11-bp sequence, which correspond to the last 11 nucleotides of attB sites, is conserved among the different bacterial species and can be considered the core of the Tn5253 integration site. Conclusions A functional characterization of the Tn5253 attB integration site combined with genome analysis contributed to elucidating the potential of Tn5253 horizontal gene transfer among different bacterial species.